SUBDIRECT INDECOMPOSABLE PARTIALLY COMMUTATIVE, NORMAL AND QUASI NORMAL ALGEBRAS - Toghanyan, V. H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2003)
In this paper are studied subdirect indecomposable, partially commutative, normal and quasinormal algebras. It is proved that the cardinality of base set ≤ 3.